Ab initio threshold displacement energies in iron. Issue 4 (1st October 2016) - Olsson, P.; Becquart, C. S.; Domain, C.
ABSTRACT: The threshold displacement energy in iron is determined using ab initio molecular dynamics. This is the most fundamental input parameter for radiation damage assessments. The predictions agree well with the available experiments and provide a significantly lower average value for iron than the standard one. This result impacts radiation damage assessments in iron alloys and steels and especially so for dose estimations and conditions close to the threshold. The importance of using an appropriate description of the core and valence electrons is highlighted. Energy loss simulations provide important fitting parameters for improved interatomic potentials. IMPACT STATEMENT Ground-breaking ab initio calculations of the threshold displacement energies in iron show significant differences in the angular anisotropy and predicted average value with respect to previous literature. GRAPHICAL ABSTRACT: